The COVID-19 Outbreak and Its Impact on Business Establishments: A Study on Challenges and Strategic Approaches - Hidalgo, Aurora G (Archīum Ateneo, 2021)
The Management Association of the Philippines (MAP) commissioned the School of Economics of the University of Asia and the Pacific (UA&P) to conduct a study aimed at understanding the impact of the COVID-19 outbreak on various industry sectors and to draw possible policy measures for both government and private institutions to help the affected sectors deal with the pandemic’s negative effects and gradually return to stable business operations. An online survey of pre-selected thirty-three (33) representatives from key priority sectors which recorded sharp contractions in the first two quarters of 2020 and which had a share to GDP of above 1 percent was conducted. To validate the survey results, stakeholder interviews were also conducted with more than 10 firms via the zoom video conferencing platform. The survey results confirmed the negative impact of the pandemic at the firm-level (i.e., decrease in employee compensation, decline in headcount, loss of revenue and other liquidity crunches, prolonged collection periods, problems in logistics, delayed or cancelled projects and disrupted supply chains and access to labor; among others). Some have had to close branches or altogether cease operations. The sudden and likely permanent shift towards digitization of operations has disrupted operations and exerted pressure to digitally transform business operations in order to survive in the so-called “new normal.” Moreover, this requires investments in equipment and training. Additional costs and investments are also needed to meet health and safety standards and protocols. Thus, required assistance commonly cited by firms were loans, subsidies, and tax relief. In the short term, the national government must restore consumer confidence and deploy its fiscal powers to stimulate aggregate demand. With assistance, business can invest in platforms and meeting health and safety protocols for workers and customers to return to work and patronize their business, whether on site or online. Resuscitating the economy is not solely the responsibility of government. It also requires solidarity and coordinated response from the private sector. Over the long term, both government and business must build more resilient organizations and strategies. This would include adopting digital transformation by both private and public sectors for a more nimble and agile economy. Business may also revisit the concept of “coopetition”. The interconnectedness of each industry calls for a more collaborative approach among businesses. When firms who have been negatively affected by the pandemic recover, this can also increase the rate at which the economy bounces back. JEL classification: O1, L1, L2